Environmental heterogeneity preference of deep-water fishes in a deep seamount (Galicia Bank) - Punzón, Antonio; Bañón, Rafael; Serrano, Alberto; Arronte, Juan Carlos; Cartes, Joan Enric; Preciado, Izaskun; Rodríguez-Cabello, C. (2012)
XIII International Symposium on Oceanography of the Bay of Biscay. ISOBAY 13, 11-13 April 2012, Santander, Spain The aim of the INDEMARES Project is to obtain information to identify valuable areas for the Natura 2000 network in the Spanish sea. One of these potential marine protected areas is the Galicia Bank, a large seamount located at 150 miles far from the west coast of Galician coast. This deep seamount have a flat summit with slight slopes from 600 m to the bank break around 1000 m. Deeper 1500 m, slope increases sharply until it reaches the abyssal platform, at 5000 m deep. During the summers of the 2010 and 2011, 20 hauls were performed in the Galicia Bank with a GOC73 otter trawl (20 mm mesh size). A total of 94 fish species were identified and two main fish assemblages were observed. One of them seemed to be associated with the Mediterranean Outflow Waters (MOW), and it was found up to 1,025 m depth. The main species (in biomass) were Hoplostethus mediterraneus, Alepocephalus bairdii, Mora moro and Scymnodon ringens. The second assemblage was located between 1,400 and 1,800 m depth, affected by the Labrador Sea Water (LSW). The main species (in biomass) were Alepocephalus bairdii, Centroscymnus coelolepis, Rouleina attrita and Halargyreus johnsonii. The species richness of the first group was higher (62 species were identified in the first group and 47 in the second). The ecological preferences of the deep-water fishes along the ontogenic development were identified, analyzing the relationships with environmental variables, topography (i.e. slope) and associated biota (i.e. presence and abundance of coral fields) Peer Reviewed